Strategic Framework for Mainstreaming Citizen Engagement in World Bank Group Operations - World Bank Group (Washington, DC, 2015)
The objective of this strategic framework is to mainstream citizen engagement in World Bank Group (WBG)-supported policies, programs, projects, and advisory services and analytics to improve their development results and within the scope of these operations, contribute to building sustainable national systems for citizen engagement with governments and the private sector. This framework will capture the diverse experiences, assess lessons learned, and outline methods and entry points to provide a more systematic and results-focused approach for the WBG. Progress toward this objective will be assessed using indicators included in program, project, and corporate results frameworks. The WBG strategy incorporates citizen engagement, including beneficiary feedback, specifically in its treatment of inclusion, which entails empowering citizens to participate in the development process and integrating citizen voice in development programs as key accelerators to achieving results. This framework builds on stocktaking and lessons learned from WBG-financed operations across regions and sectors. A key lesson is the importance of country context, government ownership, and clear objectives for citizen engagement. The approach to mainstreaming citizen engagement in WBG-supported operations is guided by five principles: 1) it is results-focused; 2) it involves engaging throughout the operational cycle; 3) it seeks to strengthen country systems; 4) it is context-specific; and 5) it is gradual. Under the right circumstances, citizen engagement can contribute to achieving development outcomes in support of the goals the WBG aims to support through all of the operations it funds: eradicating extreme poverty and boosting shared prosperity in a sustainable manner.